Glucose oxidase conjugated H2O2 sensitive CdTe QDs: an effective fluorescence tool for glucose sensing - Singh, Pooja; Prabhune, Asmita; Ogale, Satishchandra B.; Guin, Debanjan (Journal of Materials Chemistry B, 2013)
Water-soluble quantum dots (QDs) are extensively used for molecular sensing because of the flexibility they offer in terms of modification of the QDs surface with a variety of functional groups using thiol chemistry and monitoring by fluorescence intensity. We describe a simple assay that allows the photoluminescence (PL) detection of H2O2 and glucose in aqueous samples and demonstrate its applicability by estimating glucose in blood. To enable the glucose detection, we functionalized the 3-mercaptopropanoic acid (MPA) capped CdTe QDs with glucose oxidase (GOx), the enzyme specific to b-D-glucose, using carbodiimide chemistry. The fluorescence of the GOx-functionalized CdTe QDs was quenched on the interaction with glucose. The same photoluminescence quenching was also observed in gel form, when a GOx modified CdTe QDs loaded agarose gel was dipped in H2O2 and glucose solutions, respectively.

Graphene based nanocomposites for alloy (SnO2), and conversion (Fe3O4) type efficient anodes for Li-ion battery applications - Mhamane, Dattakumar; Aravindan, Vanchiappan; Taneja, Divya; Suryawanshi, Anil; Game, Onkar; Srinivasan, Madhavi; Ogale, Satishchandra B. (Composites Science and Technology, 2016)
Two types of trigol reduced one pot synthesized graphene (TRG) based nanocomposites (SnO2-TRG, and Fe3O4-TRG) are examined as potential anodes for Lithium ion battery (LIB) applications. The two specific systems represent different electrode reaction mechanisms, namely alloying, and conversion respectively. The high resolution transmission electron microscopy (HR-TEM) analysis confirms the uniform distribution of SnO2 (similar to 2 nm), and Fe3O4 (similar to 8 nm) particulates on ultrathin TRG nanosheets and highlights the importance of surfactant free synthesis. The SnO2-TRG, and Fe3O4-TRG exhibited the maximum reversible capacity of similar to 947, and similar to 1024 mA h g(-1), respectively. The results show that such graphene based composite materials can be effectively used as prospective anodes for LIB applications. (C) 2016 Elsevier Ltd. All rights reserved.